1959
DOI: 10.1111/j.1550-7408.1959.tb03926.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Calves to Reinfection with Eimeria bovis

Abstract: SYNOPSIS. An immunity to reinfection with E. bovis was demonstrated in 3 experiments involving 60 calves. This immunity develops rapidly, as indicated by resistance to a challenge given 14 days after the immunizing inoculation. In 3 groups of 3 to 6 young calves each, immunity was still present to a moderate degree 2 to 3 months after inoculation; in one group of 5 animals about a year old there was apparently a high degree of immunity about 7 months after the last inoculation. In one experiment an immunizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1962
1962
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Relatively the lower Eimeria infection during the first three months of age was due to the effect of colostral antibodies from infected cows (Fiege et al, 1992). Again the prevalence of Eimeria species infection declined after 7 months of age probably as a result of immunity development to re-infection by the same species of Eimeria (Senger et al, 1959). Cross protection between species does not occur, and hence, undoubtedly the calves might be infected by other species of Eimeria (Bangoura and Bardsley, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Relatively the lower Eimeria infection during the first three months of age was due to the effect of colostral antibodies from infected cows (Fiege et al, 1992). Again the prevalence of Eimeria species infection declined after 7 months of age probably as a result of immunity development to re-infection by the same species of Eimeria (Senger et al, 1959). Cross protection between species does not occur, and hence, undoubtedly the calves might be infected by other species of Eimeria (Bangoura and Bardsley, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…For these reasons E. maxima may be more convenient than other species are for the investigation of some aspects of immunity to coccidial infections in fowls. Senger, Hammond, Thorne, Johnson & Wells (1959) have shown that calves immune to E. bovis remained so for a period of 2-3 months, but that calves immunized when they are a year old had a high degree of resistance 7 months later. In E. maxima infection it appears that, although the immunity acquired after a single immunizing infection often develops promptly and is often complete, its duration is relatively short.…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers are discharged for 5-7 days, and smaller numbers for 2-3 weeks. In 28 calves studied by Senger et al (1959), oocysts were discharged for 7-15 days with a mean of 11.5 days. Svanbaev (1967a) found that the prepatent period was 17-18 days and the patent period no more than 10 days.…”
Section: S the Coccidiax Parasites Of Ruminantsmentioning
confidence: 99%